(549) قطاع الزراعة والري حاضره ومستقبله في خطة حتى عام 2000 The agriculture and irrigation sector: its present and future in a plan up to the year 2000 - سعد الدين الحنفي (معهد التخطيط القومي, 2026)
يستعرض الملف، دراسة استشرافية لقطاع الزراعة والري حتى عام 2000. يبدأ الملف بتسليط الضوء على الفجوة بين النمو السكاني السريع ومعدلات التنمية الاقتصادية، موضحاً أهمية القطاع الزراعي كركيزة أساسية للدخل القومي والتوظيف رغم التحديات الهيكلية التي يواجهها، مثل تفتت الملكيات الزراعية، والوسائل البدائية في الإنتاج، والزحف العمراني على الأراضي القديمة التي تبلغ مساحتها نحو 5.6 مليون فدان. كما يقدم الملف مقارنة لإحصائيات الإنتاجية بين مصر والدول المتقدمة، مشيراً إلى انخفاض إنتاجية الفدان محلياً، مرجعاً ذلك إلى مشاكل الصرف الزراعي وسوء استخدام مياه الري التي أدت لارتفاع مناسيب المياه الجوفية وملوحة التربة.، أما في الجانب التطويري، فيطرح الملف استراتيجية متكاملة تعتمد على "التوسع الرأسي" عبر تحسين كفاءة الأراضي وتعميم الميكنة الزراعية واستخدام التقاوى المنتقاة، و"التوسع الأفقي" باستصلاح أراضٍ جديدة لتصل المساحة الإجمالية المستهدفة إلى نحو 2.8 مليون فدان بحلول عام 2000. ويقترح الملف التحول من طرق الري التقليدية (الغمر) إلى أساليب حديثة مثل الري بالرش والتنقيط لتقليل الفاقد وتفادي مشكلات الصرف، مع التركيز على استصلاح مناطق "جنوب الوادي" وشواطئ بحيرة ناصر. كما يشدد الملف على ضرورة تطوير البنية التحتية للتخزين والنقل للحد من الفاقد السنوي في المحاصيل، وتحديث الهيكل التسويقي والتشريعات الزراعية لضمان استدامة التنمية الريفية. The report presents a forward-looking study of the agriculture and irrigation sector up to the year 2000. The report begins by highlighting the gap between rapid population growth and economic development rates, explaining the importance of the agricultural sector as a key pillar of national income and employment despite the structural challenges it faces, such as the fragmentation of agricultural holdings, primitive means of production, and urban sprawl on old lands, which cover an area of about 5.6 million acres. The report also presents a comparison of productivity statistics between Egypt and developed countries, noting the decline in local yield per feddan. This is attributed to agricultural drainage problems and the misuse of irrigation water, which have led to rising groundwater levels and soil salinity. On the development front, the report proposes an integrated strategy based on "vertical expansion" through improving land efficiency, widespread agricultural mechanization, and the use of improved seeds, and "horizontal expansion" by reclaiming new land, aiming to reach a total targeted area of approximately 2.8 million feddans by the year 2000. The report suggests a shift from traditional (flood) irrigation methods to modern techniques such as sprinkler and drip irrigation to reduce losses and avoid drainage problems, with a focus on reclaiming areas in Upper Egypt and along the shores of Lake Nasser. The report also emphasizes the need to develop storage and transportation infrastructure to minimize annual crop losses and to modernize the marketing structure and agricultural legislation to ensure the sustainability of rural development.